METHOD OF TEACHING POLYSEMY (WORDPLAY) (Academicia Globe: Inderscience Research, 2022)
The problem of the polysemy of a word, along with the problem of the structure of its specific meaning, has long been one of the most debated issues of semasiology and linguistics in general. In this article author tries to give feasible methods of teaching through the polysemy.